2011
DOI: 10.1371/journal.pone.0018893
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Uptake of A (H1N1) Influenza Vaccine: Findings from a Population-Based Longitudinal Study in Tokyo

Abstract: BackgroundOverall pandemic A (H1N1) influenza vaccination rates remain low across all nations, including Japan. To increase the rates, it is important to understand the motives and barriers for the acceptance of the vaccine. We conducted this study to determine potential predictors of the uptake of A (H1N1) influenza vaccine in a cohort of Japanese general population.Methodology/Principal FindingsBy using self-administered questionnaires, this population-based longitudinal study was conducted from October 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 24 publications
(34 reference statements)
2
36
3
Order By: Relevance
“…In fact, the perception of disease severity and the risk of contracting pH1N1 are the main predictors for vaccination [19][20][21]. Previous vaccination against seasonal influenza was not found in this study to be a positive predictor for the willingness to be vaccinated with the pandemic vaccine, although this has been found in a series of other studies [36][37][38][39]. In subSaharan Africa and in Côte d'Ivoire in particular, vaccination against seasonal influenza is not common among health-care providers, although quality data on vaccination coverage for seasonal influenza are very limited.…”
Section: Discussioncontrasting
confidence: 62%
“…In fact, the perception of disease severity and the risk of contracting pH1N1 are the main predictors for vaccination [19][20][21]. Previous vaccination against seasonal influenza was not found in this study to be a positive predictor for the willingness to be vaccinated with the pandemic vaccine, although this has been found in a series of other studies [36][37][38][39]. In subSaharan Africa and in Côte d'Ivoire in particular, vaccination against seasonal influenza is not common among health-care providers, although quality data on vaccination coverage for seasonal influenza are very limited.…”
Section: Discussioncontrasting
confidence: 62%
“…25 Recommendations which are not supported through public funding mechanisms may decrease the uptake of the vaccine. 26 Health care system related factors such as lack of reminder-recall systems, immunization records, computerized vaccine registries and vaccine delivery systems might be other factors that contribute to low vaccine coverage rates. 27 A review evaluating the effectiveness of interventions to improve targeted vaccination coverage for influenza, pneumococcal, and hepatitis B vaccines reported that provider reminder systems were the only strategy identified to be effective when implemented alone.…”
Section: Discussionmentioning
confidence: 99%
“…Government policy mandated that subjects with a higher risk of influenza infection had a priority of vaccination during the 2009 influenza A (H1N1) pandemic [16]. Vaccination rates during the 2009/2010 season were higher in adults with than without underlying disease in Japan [17]. Vaccination rates have also been shown higher in high risk group adults [7].…”
Section: Uchida / J Infect Chemother XXX (2017) 1e4mentioning
confidence: 99%